KETIKA ENERGI MENENTUKAN JUARA: TINJAUAN FISIOLOGI OLAHRAGA TENTANG SISTEM ENERGI - Ilham Kamaruddin; Ega Pangalingan; A.Muh.Dzakwan Mangawiang; Nasyarullah, Acep; Usman Ali; Baharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of energy systems in determining athletic performance through a systematic literature review approach. Energy systems in sports consist of the ATP PC system, anaerobic glycolysis, and the aerobic system, each contributing differently depending on exercise intensity and duration. The method used in this study is a systematic review of 15 national scientific sources, including journals and books related to exercise physiology, VO2Max, and metabolic energy systems. The results show that the ATP PC system dominates short duration and high intensity activities, while anaerobic glycolysis supports moderate intensity efforts, and the aerobic system plays a major role in long duration activities. In addition, VO2Max is identified as a key indicator of aerobic capacity that significantly influences endurance and recovery ability. Environmental factors and training methods such as interval training also contribute to optimizing energy system efficiency. The findings indicate that the integration of all energy systems is essential in supporting optimal athletic performance. Therefore, understanding exercise physiology and energy systems is crucial in designing effective and structured training programs to improve athlete performance.